Analysis of causes of failure of aviation transport systems - Павлов, В. В.; Скрипец, А. В.; Павлова, С. В. (Proceedings of National Aviation University (archive), 1998)
The concept of completion of systems allows to reveal the causes of disintegration of organized transport flows that results in catastrophe on transport. It is shown that the cause of this effect is the "profitability syndrome"